A linear chain of carbazolyl-bis(tetrazole) supported copper(II) dimers held together by bridging tribromide anions. Issue 15 (3rd August 2019) - Jie, Huang; Gajecki, Leah; Berg, David J.; Oliver, Allen G.
Abstract: Reaction of NaCzT iPr with CuBr, followed by exposure to air, results in formation of {[Cu( κ 3 -N3 -μ - N' -CzT iPr )( μ -OH)]2 [ μ -Br3 ]}x, 2 . The structure of 2 in the solid state consists of hydroxo-bridged Cu(II) dimers connected into a linear chain polymer by bridging Br3 – units. The Cu(II) centers have axially elongated coordination with a Br3 – terminus and a bridging N from a tetrazole on the adjacent Cu forming the ligands on the long axis. The Br3 – unit is linear with short Br–Br distances while the Cu–Br–Br angle is close to 90°. The reaction involves oxidation of both the Cu(I) and Br – of CuBr in air. Graphical Abstract: